Incidence, risk factors, management strategies, and outcomes of antibody-mediated rejection in pediatric kidney transplant recipients: a multicenter analysis of the Cooperative European Paediatric Renal Transplant Initiative (CERTAIN) - Fichtner, Alexander; Gauché, Laura; Süsal, Caner; Tran, Thuong Hien; Waldherr, Rüdiger; Krupka, Kai; Guzzo, Isabella; Carraro, Andrea; Oh, Jun; Zirngibl, Matthias; Weitz, Marcus; König, Jens; et al. (Pediatric nephrology, 2025)
This study by the Cooperative European Paediatric Renal Transplant Initiative (CERTAIN) was designed to determine the incidence, risk factors, current management strategies, and outcomes of antibody-mediated rejection (ABMR) in pediatric kidney transplant recipients (pKTR).
Online verfügbar: 16. September 2024
Gesehen am 28.04.2025